Integrated Hospital–Territory Organizational Models and the Role of Family and Community Nurses in the Management of Chronic Conditions: A Scoping Review - Gianluca Azzellino; Patrizia Vagnarelli; Mauro Passamonti; Luca Mengoli; Lia Ginaldi; Massimo De Martinis (Medicina)
Background and Objectives: One of the challenges of modern healthcare systems, in terms of economic and organizational sustainability and the impact on patients’ quality of life, is the progressive increase in chronicity and care complexity. In this scenario, hospital–community integration models represent possible strategies to ensure the continuity of care, reduce readmission rates, and improve clinical outcomes. This study aims to map integrated care models for patients with chronic diseases, with active involvement of the family and community nurse, describing their functions and associated clinical, organizational, and economic outcomes, as well as barriers and facilitators to their implementation. Materials and Methods: The review was conducted using the JBI methodology and the PRISMA-ScR protocol and identified 26 studies with a publication range from 2000 to 2025. Results: The emerging results highlight the use of integrated and personalized organizational models in the post-discharge phases, with a leading role for the family and community nurse in the assessment, planning, and coordination of various steps. Conclusions: The interventions are associated with an increase in patient and caregiver satisfaction, a reduction in outcomes such as the rehospitalization rate, and greater continuity of care.